Nursing care for indigenous elderly people with hypertension: A scoping review protocol (Research, Society and Development, 2024)
Objective: To map scientific evidence on nursing care for indigenous elderly people with hypertension in the global scenario. Methodology: Protocol based on the recommendations of the Joanna Briggs Institute (JBI). The search for studies will be carried out from December 2023 to July 2024, with no time frame, in databases and electronic libraries such as LILACS, MEDLINE/via PubMed, CINAHL, Scopus, EMBASE, Web of Science, BDENF, SciELO, the Capes catalogue of theses and dissertations and Europa OpenGrey, the latter two being referred to as grey literature.  The reviewers will consist of two reviewers who will work independently and one reviewer who will decide on disagreements or doubts. Expected outcome: The results of the review will be presented descriptively. It is hoped to find scientific evidence on nursing care for this population. Conclusion: This study presents the development of a reproducible model that highlights in detail the stages of a scoping review protocol, following all the precepts and scientific rigor.